2019
DOI: 10.15694/mep.2019.000148.1
|View full text |Cite
|
Sign up to set email alerts
|

DOES EXPERIENCE MATTER? A mixed methods study of medical student experiences of near-peer and senior clinician-led tutorials

Abstract: The primary aim of the study was to determine whether classroom-based acute care teaching delivered by junior doctors is comparable to that by senior doctors or faculty. This study reviews student opinions of near-peer and faculty led teaching on acute medicine to explore the differences and student preferences. Methods:This study aimed to evaluate the role of trainees as near-peer tutors in the acute medicine tutorial based setting by randomly allocating the sessions to a junior or senior doctor. Student opin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…17,27 Peers are considered more approachable and have greater familiarity with challenges students face. 16,28 These findings are consistent with Lopez et al 19 who reported that incoming dental students value support from students who had recently gone through the same transition. However, some mentoring relationships were hindered by the informal program design as it relied on shared assumptions and motivations about mentoring roles and responsibilities.…”
Section: Discussionsupporting
confidence: 85%
“…17,27 Peers are considered more approachable and have greater familiarity with challenges students face. 16,28 These findings are consistent with Lopez et al 19 who reported that incoming dental students value support from students who had recently gone through the same transition. However, some mentoring relationships were hindered by the informal program design as it relied on shared assumptions and motivations about mentoring roles and responsibilities.…”
Section: Discussionsupporting
confidence: 85%